Evidence of Diel Vertical Migration of Mesopelagic Sound-Scattering Organisms in the Arctic - Gjøsæter, Harald; Wiebe, Peter H.; Knutsen, Tor; Ingvaldsen, Randi B. (Frontiers in Marine Science, 2017)
While sound scattering layers have been described previously from ice-covered waters in the Arctic, the existence of a viable mesopelagic community that also includes mesopelagic fishes in the Arctic has been questioned. In addition, it has been hypothesized that vertical migration would hardly exist in these areas. We wanted to check if deep scattering layers (DSLs) was found to the west and north of Svalbard (79°30’N - 82°10’N) during autumn 2015, and if present; whether organisms in such DSLs undertook vertical migrations. Our null hypothesis was that there would be no evidence of diel vertical migration. Multi-frequency acoustic observations by hull mounted echosounders (18, 38 and 120 kHz) revealed a DSL at depths ~210-510 m in areas with bottom depths exceeding ~600 m. Investigating eight geographical locations that differed with respect to time periods, light cycle and sea ice conditions, we show that the deeper layer of DSL displayed a clear ascending movement during night time and a descending movement during daytime. The high-light weighted mean depth (343-514 m) with respect to backscattered energy was statistically deeper than the low-light weighted mean depth (179-437 m) for the locations studied. This behavior of the DSL was found to be consistent both when the sun was continuously above the horizon and after it started to set on 1 September, and both in open water and sea ice covered waters. The weighted mean depth showed an increasing trend, while the nautical area backscattering strength from the DSL showed a decreasing trend from south to north among the studied locations. Hydrographic observations revealed that the diel migration was found in the lower part of the north-flowing Atlantic Water, and was disconnected from the surface water masses above the Atlantic Water during day and night. The organisms conducting vertical migrations were studied by vertical and oblique hauls with zooplankton nets and pelagic trawls. These data suggest that these organisms were mainly various mesopelagic fishes, some few larger fishes, large zooplankton like krill and amphipods, and various gelatinous forms.